22+5(x+3)=

Simple and best practice solution for 22+5(x+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 22+5(x+3)= equation:


Simplifying
22 + 5(x + 3) = 0

Reorder the terms:
22 + 5(3 + x) = 0
22 + (3 * 5 + x * 5) = 0
22 + (15 + 5x) = 0

Combine like terms: 22 + 15 = 37
37 + 5x = 0

Solving
37 + 5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-37' to each side of the equation.
37 + -37 + 5x = 0 + -37

Combine like terms: 37 + -37 = 0
0 + 5x = 0 + -37
5x = 0 + -37

Combine like terms: 0 + -37 = -37
5x = -37

Divide each side by '5'.
x = -7.4

Simplifying
x = -7.4

See similar equations:

| 2x+0=0x-2 | | h(t)=-16t^2+33.1t+122.56 | | 11(x-4)= | | 8w-8=w+20 | | (x+4)2=75 | | 9w+2=8w-8 | | 6x^2-21x+20=0 | | x+2+28=x+1 | | A+12-8=26 | | 7x-7=x+11 | | 2x-15=3x-15 | | 9w+2=w+20 | | -[6x-(3x+1)]=-4-[4(2x-3)-3x] | | H(t)=-16t^2+33.1t+1.7 | | 7+b-8=12 | | m+7=3+4 | | 14-2(3x+6)= | | 6x-3y+37=11-y | | -g+2(3+g)=-4(g-4) | | 2[w-(2w+10)+8]=2(w+2) | | 5(y-2)=6(y-1) | | 3(2k+18)=6(9+k) | | 4x^2+56x+156=0 | | s=4s-60 | | 9x-20=7x+16 | | 140=(2x-2)(2x+2) | | 6(5-5y)= | | t^3+t=4930 | | 2z/2= | | 11+x+24=19+x+22 | | 0.75(4x+8)=-3 | | 5k-15+j=3j-5 |

Equations solver categories